"Was German Fascism a Utopia?" - Hermand, Jost (My University, 2007)
In collaboration with the University of Wisconsin-Madison's Institute for Research in the Humanities, the Center for the Humanities continues the lecture series Focus on the Humanities which illuminates and celebrates the work of outstanding members of the UW-Madison humanities faculty by bringing their current research to the broader Madison community.
Please note that due to technical difficulties only the first half hour of this lecture was recorded. Jost Hermand earned his Ph.D. in 1955 from the University of Marburg, Germany. He has been teaching at the UW since 1955, has been a Vilas Research Professor since 1967, and retired in 2004. He is honorary professor at the Humboldt University in Berlin, Germany. Relevant publications include: Deutsche Kulturgeschichte des 20. Jahrhunderts (2006), A Hitler Youth in Poland: The Nazi Children's Evacuation Program in World War II (1997), Old Dreams of a New Reich: Volkish Utopias and National Socialism (1992).
Keywords: Center for the Humanities; Focus on the Humanities; German; fascism; Jost Hermand